Xiongshao Zhitong Recipe Attenuates Nitroglycerin-Induced Migraine-Like Behaviors via the Inhibition of Inflammation Mediated by Nitric Oxide Synthase - Yang, Song; Chen, Cong; Liu, Xiaoyao; Kang, Qianjun; Ma, Quantao; Li, Pin; Hu, Yujie; Li, Jialin; Gao, Jian; Wang, Ting; Wang, Weiling (Frontiers in Pharmacology, 2022)
Migraine was one of the main causes of disability worldwide, particularly in young adult and middle-aged women. Xiongshao Zhitong Recipe (XZR) is a traditional Chinese medicine used for treating migraine, while its bioactive components and therapeutic mechanisms remained unclear. We aimed to confirm the therapeutic effect of XZR on migraine and discovere the possible mechanism and bioactive components of XZR. Here, a sensitive UHPLC-LTQ-Orbitrap MS assay was carried out for analyzing the ingredients of XZR and a total of 62 components were identified in XZR, including coumarin, phenolic acids, phthalides, flavonoids and terpenoids; among them, 15 components were identified in the serum samples after XZR treatment. We established migraine rat model via injection of nitroglycerin (NTG). The in vivo experiments demonstrated that XZR attenuated the allodynia and photophobia in NTG-induced migraine rats and XZR also demonstrated analgesic effects as evidenced by the reduction of the writhing frequency during the acetic acid-induced writhing model. XZR reversed the abnormal level of nitric oxide, 5-hydroxytryptamine (5-HT), calcitonin gene-related peptide (CGRP) and substance P (SP) to normal level. XZR also downregulated inflammatory reaction, including mast cell degranulation and serum IL-1β, IL-6 and TNF-a content. In terms of mechanism, we revealed that XZR treated NTG-induced migraine through inhibition of neuron nitric oxide synthase (nNOS) and inducible nitric oxide synthase (iNOS) expression in both trigeminal nucleus caudalis (TNC) and periaqueductal gray matter (PAG) and total NOS enzyme activity, which regulated NF-κB signaling pathway. Additionally, imperatorin and xanthotoxin, two major ingredients from XZR, showed a high binding affinity to nNOS (Gly468-Leu616). In vitro, XZR, imperatorin and xanthotoxin inhibited nNOS expression and NF-κB signaling pathway in LPS-stimulated PC12 cells. In conclusion, we demonstrated the therapeutic effects of XZR and provided evidence that XZR played a critical role in anti-inflammation via suppressing NOS and NF-κB signaling pathway activation. Imperatorin and xanthotoxin were the potential bioactive components of XZR. This study supported that XZR was a candidate herbal drug for migraine therapy.